2019
DOI: 10.1093/mnras/stz1952
|View full text |Cite
|
Sign up to set email alerts
|

Is the dark-matter halo spin a predictor of galaxy spin and size?

Abstract: The similarity between the distributions of spins for galaxies (λ gal ) and for dark-matter haloes (λ halo ), indicated both by simulations and observations, is naively interpreted as a one-to-one correlation between the spins of a galaxy and its host halo. This is used to predict galaxy sizes in semi-analytic models via R e ≃ λ halo R vir , where R e is the half-mass radius of the galaxy and R vir is the halo radius. Utilizing two different suites of zoom-in cosmological simulations, we find that λ gal and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
121
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 87 publications
15
121
0
Order By: Relevance
“…with A = 0.02, n = 1, γ = −0.7, R 0 = 1 kpc, and halo concentration c measured as a function of redshift, fits the hydrodynamic simulation results in Jiang et al (2019) with a residual scatter of ∼ 0.15 dex. This relation implies that more concentrated halos host less extended stellar systems at fixed virial radius in these simulations.…”
Section: A4 Tidal Strippingsupporting
confidence: 59%
“…with A = 0.02, n = 1, γ = −0.7, R 0 = 1 kpc, and halo concentration c measured as a function of redshift, fits the hydrodynamic simulation results in Jiang et al (2019) with a residual scatter of ∼ 0.15 dex. This relation implies that more concentrated halos host less extended stellar systems at fixed virial radius in these simulations.…”
Section: A4 Tidal Strippingsupporting
confidence: 59%
“…The observational complexities require a thorough understanding of the systematics. The strong spin correlation between disk galaxies and their parent halos is confirmed in hydrodynamic simulations [24,31], so in this Letter we use halos to represent galaxies. Strong Lagrangian-Eulerian spin correlation has also been confirmed in this work and many high-resolution N -body simulations [19][20][21]23].…”
mentioning
confidence: 75%
“…Recently, Jiang et al (2019) used cosmological hydrodynamical simulations to study the relation between the specific angular momentum of galaxies and dark matter halos and found evidence for a weak correlation, due to a combination of complex phenomena that lead to the formation of galaxies (see also Danovich et al 2015). These results are potentially very interesting since they revisit the physical basis of the MMW98 study; however, it has yet to be demonstrated whether they can reproduce the observed Fall relation since from their main result j / j h ∝ λ −1 , it would follow that j ∝ M 2/3 h -because λ ∝ j h /M 2/3 h -which is not compatible with observations of the Fall relation, unless in the case of a quasi-linear stellar-tohalo mass relation (M ∝ M h ) which is excluded by the data (Posti et al 2019a).…”
Section: Limitations Of Our Modelmentioning
confidence: 99%